Evaluation of sexual dysfunction in gynecologic cancer survivors using DSM-5 diagnostic criteria - Hao Lin; Hung-Chun Fu; Chen-Hsuan Wu; Yi-Jen Tsai; Yin-Jou Chou; Chun-Ming Shih; Yu-Che Ou (BMC, 2022)
Abstract Background In gynecologic cancer survivors, female sexual dysfunction (FSD) remains under-investigated. We attempted to estimate the prevalence of FSD associated with distress in gynecologic cancer survivors using diagnostic and statistical manual of mental disorders fifth edition (DSM-5) diagnostic criteria and to identify women at risk for FSD. Methods We conducted a cross-sectional analysis of premenopausal women aged 20-50 with various gynecologic cancers at least one year after treatment between January 2017 and December 2019. Data of sociodemographics and physical conditions were collected via face-to-face interview during outpatient clinic visits. The domains we used to define FSD were based on DSM-5 diagnostic criteria. Statistical analysis was carried out using Student's t test, Chi-square test and multiple logistic regression. Results A total of 126 gynecologic cancer survivors with a mean age of 42.4 years were included for analysis and 55 of them (43.7%) were diagnosed as having FSD associated with distress based on DSM-5 criteria. More than half of women (65.1%) reported decreased sexual satisfaction after cancer treatment. According to DSM-5 definition, the most common female sexual disorders were sexual interest/arousal disorder (70.9%), followed by genitopelvic pain/penetration disorder (60.0%), and orgasmic disorder (20.0%). In multiple logistic regression model, endometrial cancer diagnosis was the only independent factor predicting less influence of cancer treatment on FSD (OR 0.370; 95% CI 0.160, 0.856). Conclusion The first study to use DSM-5 criteria for estimation of FSD prevalence. This enables clinicians to identify which women are actually needed to seek medical help. A prevalence of 43.7% of FSD associated with distress was found in a group of gynecologic cancer survivors with the most common being sexual interest/arousal disorder. Endometrial cancer survivors were at low risk for developing FSD after treatment.